Pengaruh Metode Mind Mapping terhadap Hasil Belajar Bahasa Indonesia pada Materi Menulis Cerita Pendek Kelas V di SDN Mangunharjo 3 - Sri Lestari; Kartika Septianingrum; Miratu Chaeroh (LP. Ma'arif Janggan Magetan, 2024)
This study delves into the impact of employing the Mind Mapping technique on the proficiency of fifth-grade students in crafting short stories within the Indonesian language curriculum at SDN Mangunharjo 3 Ngawi. Employing a quantitative approach, the research adopts the True Experimental Design format. This experimental method meticulously assesses the influence of an independent variable (the treatment) on a dependent variable (the outcome) under controlled circumstances. With a focus on sample representation, all participants partake as respondents, utilizing a saturated sampling technique. The findings underscore a notable enhancement in students' narrative composition skills when utilizing the Mind Mapping technique, as evidenced by the Paired Sample t-Test analysis. The statistical analysis reveals a significant disparity, as indicated by the sig value (2-tailed) of 0.003, falling below the threshold of 0.005. Consequently, the null hypothesis (H0) is refuted, while the alternative hypothesis (Hadi) is validated, affirming the significant influence of Mind Mapping in this instructional context. So the conclusion of this research is that the experimental group as a treatment group used the mind mapping method more effectively.